PERTUMBUHANDANPERUBAHANSTRUKTURSEKTOR PERT ANIAN PROVINSI JAWA TENGAH SEBELUM DAN SETELAH OTONOMI DAERAH - Maria Maria; Irham Irham; Djuwari Djuwari (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2008)
The research objectives to know: (1) alteration structural of agricultural sector in Central Java compared to alteration of national agricultural sector chartered investment council structure before and after decentralization; (2) identification of pledge agricultural sector in improvement of economic growth rate regional in Central Java before and after decentralization; (3) velocity and growth typology of Central Java agricultural sector before and after decentralization. This research applies descriptive analytical method and data used are GRDP Central Java andGDP National during 1995-2005 based on constant price of 2000. Growthaverage speed offield crop, plantation and breeding, andforestry improvedafter the decentralization was implemented, while growth average speed offishery sector decreasing. LQ and DLQ analyses show that field crop andbreeding sectors are still expected to be basis sector before decentralization. After decentralization was implemented, field crop and breeding remain to be basis, while plantation crop andforestry experiences reposition from non basis towards basis. Klassen Typology analysis shows that field crop and breeding are fast growth before decentralization. After decentralization, plantation crop and forestry classified as fast growth sector. The speed growth of food crops, plantation, breeding, and forestry accelerated after decentralization, whilefishery sector is relatively lags.